2010
DOI: 10.1111/j.1365-2958.2009.06969.x
|View full text |Cite
|
Sign up to set email alerts
|

Three new RelE‐homologous mRNA interferases of Escherichia coli differentially induced by environmental stresses

Abstract: Prokaryotic toxin – antitoxin (TA) loci encode mRNA interferases that inhibit translation, either by cleaving mRNA codons at the ribosomal A site or by cleaving any RNA site-specifically. So far, seven mRNA interferases of Escherichia coli have been identified, four of which cleave mRNA by a translation-dependent mechanism. Here, we experimentally confirmed the presence of three novel TA loci in E. coli. We found that the yafNO, higBA (ygjNM) and ygiUT loci encode mRNA interferases related to RelE. YafO and Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
210
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(219 citation statements)
references
References 66 publications
8
210
1
Order By: Relevance
“…The antitoxins that regulate the activities of the mRNases are Lon substrates (21,27,28). Consequently, Lon is required for activation of the mRNases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The antitoxins that regulate the activities of the mRNases are Lon substrates (21,27,28). Consequently, Lon is required for activation of the mRNases.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, if an mRNase is in excess of its cognate antitoxin, the mRNase destabilizes the promoter-operator complex, and thereby induces TA operon transcription (26). The TA operons of E. coli that encode mRNases are induced by amino acid starvation via a Lon (Long Form Filament)-dependent mechanism (21,27,28). Direct evidence of Lon degradation of antitoxins has been obtained for RelB, MqsA, and YefM (27,29) (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we determined the crystal structures of MqsA alone and the MqsR⅐MqsA complex and showed that the mqsRA operon defines a novel family of TA systems in E. coli, in which MqsR is the toxin and MqsA is the antitoxin (19). The structure revealed that the MqsR toxin is a ribonuclease belonging to the RelE bacterial toxin family (19,34,35). MqsR is unique because it is the first toxin linked to biofilms and quorum sensing (33) and is the first toxin that, when deleted, decreases persister cell formation (31).…”
mentioning
confidence: 99%